2019
DOI: 10.1080/0886022x.2018.1562356
|View full text |Cite
|
Sign up to set email alerts
|

The effectiveness of cinacalcet: a randomized, open label study in chronic hemodialysis patients with severe secondary hyperparathyroidism

Abstract: Background: Secondary hyperparathyroidism (SHPT) is associated with high incidences of cardiovascular disease, bone fracture, and mortality. This study was conducted to demonstrate the effectiveness of cinacalcet treatment on chronic kidney disease-mineral bone disorder (CKD-MBD) markers in chronic hemodialysis patients with severe SHPT. Methods: In phase 1, 30 adult HD patients were randomized to cinacalcet or control groups for 12 weeks to explore the achievement of >30% re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
21
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 39 publications
4
21
0
1
Order By: Relevance
“…The present results showed that the FGF23 level decreased to approximately 50% in all sub-groups of each arm, which is consistent with the EVOLVE study of cinacalcet. 28 However, the FGF23 levels were somewhat variable, which is consistent with previous studies, 24,26,27 indicating that other factors, likely uncontrolled for in the present analysis and in previous studies, may be involved in the regulation of serum intact FGF23 level. Given the accumulating evidence to suggest a significant association between elevated FGF23 and cardiovascular disease, [28][29][30] the decreasing trend in FGF23 level observed after treatment with evocalcet and cinacalcet may be a beneficial effect.…”
Section: Evocalcetsupporting
confidence: 91%
See 1 more Smart Citation
“…The present results showed that the FGF23 level decreased to approximately 50% in all sub-groups of each arm, which is consistent with the EVOLVE study of cinacalcet. 28 However, the FGF23 levels were somewhat variable, which is consistent with previous studies, 24,26,27 indicating that other factors, likely uncontrolled for in the present analysis and in previous studies, may be involved in the regulation of serum intact FGF23 level. Given the accumulating evidence to suggest a significant association between elevated FGF23 and cardiovascular disease, [28][29][30] the decreasing trend in FGF23 level observed after treatment with evocalcet and cinacalcet may be a beneficial effect.…”
Section: Evocalcetsupporting
confidence: 91%
“…These findings are consistent with those observed following treatment with other calcimimetics. 26,27 Although further studies are needed, evocalcet and cinacalcet appear to improve bone metabolism with dialysate calcium concentrations of 2.5 to 3.0 mEq/L.…”
Section: Discussionmentioning
confidence: 99%
“…22 Hyperphosphatemia in dialysis patients continues to represent a major challenge, and there is evidence associating serum phosphate concentrations with mortality. 23 The majority of the respondents used cinacalcet for cases of refractory hyperparathyroidism (48.5 %), or for cases of hyperparathyroidism with hypercalcemia (39%). However, a significant percentage of the respondents were using cinacalcet as second agent (9%).…”
mentioning
confidence: 99%
“…Existing treatment strategies have the potential to elevate serum levels of calcium, which is considered an independent predictor of poor cardiovascular outcomes as a result of metastatic calcification. 23 The majority (77.8%) of nephrologists considered low serum calcium (<2.1 mmol/L) as a contraindication to commence cinacalcet while the remaining opted to use calcium supplements with cinacalcet in cases of hypocalcemia. It is widely accepted that hypocalcemia is a contraindication for cinacalcet use.…”
mentioning
confidence: 99%
See 1 more Smart Citation